Intermediate Teacher's Math Activities Kit : Includes 100 ready to use lessons and activity sheets covering six areas of the 4-6 math curriculum - Micklo, Stephen J. (Jossey-Bass, 2005)
ix, 310 p. : Ill.; 29 cm